2010
DOI: 10.1002/bjs.7255
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic right hemicolectomy

Abstract: Single-incision laparoscopic surgery is a possible approach to right colonic resection with potential for minimal access advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38].…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently reported single-incision operation in colorectal surgery has been right hemicolectomy. After first being described in 2008 [19,20], multiple case reports and series have demonstrated the safety and feasibility of right hemicolectomy [21][22][23][24][25][26][27][28][29]. Case-control studies of single-incision laparoscopic right colectomy have demonstrated the technique to be equivalent to conventional laparoscopic surgery with a small cosmetic benefit [30][31][32].…”
mentioning
confidence: 96%
“…Only a few single-incision laparoscopic colorectal procedures have been performed for inflammatory bowel disease (IBD), mostly sporadically, while some singleinstitution series have been published for segmental resection for malignant disease [12,14,16,17,26,43]. This may be because of the well-known technical difficulties that IBD may cause, in addition to the patients' general condition-often debilitated and under corticosteroids and other immunosuppressive drugs-and the magnitude of the surgical procedures [44].…”
Section: Discussionmentioning
confidence: 97%